Peningkatan Angka Kejadian Nyeri Kepala Primer Terhadap Kualitas Tidur Buruk Pada Mahasiswa Fakultas Kedokteran Universitas Nusa Cendana Tahun 2020 - Landa, Destrini Anjani; Sp.OT, dr. Su Djie To Rante, M. Biomed,; FISCM, dr. S.M.J. Koamesah., MMR.,MMPK FISPH., (Universitas Nusa Cendana, 2023)
Abstract Background: According to the World Health Organization (WHO) about 90% of the world’s adult population experience headache at least once a year. Globally, it is estimated that headache prevalence in adults is around 50-75% for the age range of 18-65 years old. One of the risk factors for headache is sleep disturbance. The frequency, intensity, and onset of headaches have a significant association with the incidence of sleep disturbances, including nightmares, difficulty falling asleep, waking up too early, and poor sleep quality. These sleep disturbances are caused by changes in neurotransmitters such as serotonin and melatonin that disrupt the circadian rhythm. The Medical Faculty student group is relatively prone to having poor sleep quality. This can be caused by the high duration and intensity of learning, doing tasks that require extra energy and concentration. Objective: To determine the relationship between sleep quality and the incidence of primary headache in students of the Faculty of Medicine, the University of Nusa Cendana in 2020. Methods: This study was an observational analytic study that employed a cross-sectional design conducted on preclinical students of the Faculty of Medicine, the University of Nusa Cendana using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and the primary headache questionnaire. The sampling technique used stratified random sampling with a total of 74 respondents who met the inclusion and exclusion criteria. The study was analyzed by univariate, bivariate using the chi-square test. Results: From 74 respondents, it was found that 54 respondents (73%) had poor sleep quality and 20 respondents (27%) had good sleep quality. From 74 respondents, 51 respondents (68.9%) also had a primary headache and 23 respondents (31.1%) did not have a primary headache. The results of the bivariate analysis test in this study obtained p = 0.007 (p <0.05) and the RR (Relatif Risk) value for poor sleep quality on headache is 2.475 or 2 times (RR> 1) which means that the variable studied is a risk factor. Conclusion: There is a significant relationship between sleep quality and the incidence of primary headaches in students of the Faculty of Medicine, the University of Nusa Cendana in 2020. Keywords: sleep quality1, primary headache2, medical students3